Uma interpretação da Convenção UNESCO de 2001 sobre proteção do patrimônio cultural subaquático: reflexões acerca do direito internacional e do direito brasileiro. - Sartori, Marcelo Vanzella (2015)
The UNESCO Convention on protection of underwater cultural heritage 2001 gives rise to research about what actually needs to be understood as goods that integrate with such a concept, widening the interest in the subject and determining the reasons, why economic, cultural moment, that international States point as paramount to defend their interests and international cooperation exercise strategy. Faced with such basic international legal apparatus, this research is based on a survey of the essential concepts about international regimes and the possible alignment of the issue of protection of underwater cultural heritage to those purposes, because the sources of international environmental law are used as tools for the ongoing implementation of protection of these cultural goods. Thus, the UNESCO Conventions analysis of cultural heritage, broadly indicate a rich and evolving international apparatus of protection of such goods internationally recognized. We highlight the current detailed analysis and practical situation of the terms of the UNESCO 2001 Convention, analyzing their key concepts, States Parties and non-Parties and the international trusteeship character of underwater cultural heritage. After the UNESCO Convention instrumental cut 2001, promotes the removal of the Brazilian domestic legal apparatus on the protection of underwater cultural heritage, which is shown in position contrary to international order negotiations, clashing the Brazilian presence in the international scenario, in other optics, is well regarded. Criticizes Brazil's current legislative situation in this respect, proposing to involvement in the signing and ratification of the UNESCO 2001 Convention.